Advances and Developments in Strategies to Improve Strains of Saccharomyces cerevisiae and Processes to Obtain the Lignocellulosic Ethanol-A Review - Laluce, Cecília [UNESP]; Schenberg, A. C. G.; Gallardo, J. C. M. [UNESP]; Coradello, L. F. C. [UNESP]; Pombeiro-Sponchiado, S. R. [UNESP] (Humana Press Inc, 2012)
The conversion of biomass into ethanol using fast, cheap, and efficient methodologies to disintegrate and hydrolyse the lignocellulosic biomass is the major challenge of the production of the second-generation ethanol. This revision describes the most relevant advances on the conversion process of lignocellulose materials into ethanol, development of new xylose-fermenting strains of Saccharomyces cerevisiae using classical and modern genetic tools and strategies, elucidation of the expression of some complex industrial phenotypes, tolerance mechanisms of S. cerevisiae to lignocellulosic inhibitors, monitoring and strategies to improve fermentation processes. In the last decade, numerous engineered pentose-fermenting yeasts have been developed using molecular biology tools. The increase in the tolerance of S. cerevisiae to inhibitors is still an important issue to be exploited. As the industrial systems of ethanol production operate under non-sterile conditions, microbial subpopulations are generated, depending on the operational conditions and the levels of contaminants. Among the most critical requirements for production of the second-generation ethanol is the reduction in the levels of toxic by-products of the lignocellulosic hydrolysates and the production of low-cost and efficient cellulosic enzymes. A number of procedures have been established for the conversion of lignocellulosic materials into ethanol, but none of them are completely satisfactory when process time, costs, and efficiency are considered.
Keywords: Biomass pretreatments and hydrolysis; Pentose-fermenting yeasts; Pentose metabolism in yeast; Yeast tolerance to biomass hydrolysates; Genes related to yeast stresses; Yeast diversity and dynamics; Saccharomyces cerevisiae